IN THE ERA OF GIG ECONOMY: ARE UBER DRIVERS CONTACTORS OR EMPLOYEES? - Mohammed Al Bhadily (PEOPLE: International Journal of Social Sciences, 2025)
The evolving dynamics of the employment relationship highlight inherent power imbalances between employers and employees, often leaving workers vulnerable to exploitation. This paper explores the intersection of technological advancements and workers’ rights, focusing on app-based gig economy platforms like Uber. By classifying drivers as independent contractors, Uber denies them essential employee benefits such as minimum wages, sick leave, and redundancy protections. The paper evaluates the implications of this classification through a comparative analysis of international legal initiatives, including the reclassification of Uber drivers as workers in the UK, legislative measures in U.S. states like California and New York, and a collective bargaining agreement in Denmark. These cases demonstrate varying approaches to safeguarding gig workers’ rights amidst modern technological challenges. The paper further examines the potential applicability of these legal frameworks to Australia, addressing local legislative contexts and the gig economy’s impact on fair employment standards. Drawing lessons from global precedents, this research proposes effective strategies to ensure equitable treatment of Uber drivers in Australia.